Role of Nanotechnology in the Management of Rheumatoid Arthritis - Mustafa, Faheem; Ajmal, Ramsha; Salam, Hafsa; Binti Umar, Rabiatul Adawiyah; Binti Che Taha, Che Suhaili; Binti Wan Taib, Wan Rohani; Chopra, Shivani; Chopra, Hitesh (Scripta Medica, 2025)
Rheumatoid arthritis (RA) is a debilitating autoimmune disease characterised by chronic inflammation of synovial joints, resulting in pain, stiffness and potential joint and bone damage. Left untreated, RA significantly impacts daily life and may lead to severe disability or death. Early diagnosis is critical to curbing disease progression and reducing inflammation and joint damage. Traditional drug therapies, although effective, often pose severe side effects, prompting interest in alternative and complementary approaches. Nanotechnology, particularly nanoparticles, has emerged as a transformative tool in RA management, offering enhanced drug delivery, improved diagnostic precision and reduced systemic side effects. This review explores the multifaceted role of nanotechnology in RA diagnosis and treatment, emphasising the synergistic potential of nanomedicine and natural compounds. Existing knowledge gaps and future research directions in leveraging nanotechnology for RA treatment are also discussed.